2019
DOI: 10.1111/mpp.12819
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of an outbreak of the potato late blight pathogen, Phytophthora infestans, reveals both clonality and high genotypic diversity

Abstract: Summary An outbreak of the potato late blight pathogen Phytophthora infestans in Denmark was characterized in order to resolve the population structure and determine to what extent sexual reproduction was occurring. A standard set of microsatellite simple sequence repeats (SSRs) and single nucleotide polymorphism (SNP) markers generated using restriction site‐associated DNA sequencing (RAD‐seq) were employed in parallel. A total of 83 individuals, isolated from seven different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Preferences of particular isolates to produce either antheridia or oogonia in heterothallic species have been recorded; however, bisexuality is hypothesised in homothallic species [ 29 ], therefore, the possibility of the mating of two isolates of homothallic species cannot be excluded. Outbreeding was documented in either heterothalic P. infestans [ 30 , 31 , 32 ] or P. ramorum [ 33 ], or in homothallic species such as P. sojae and P. porri . In homothallic Phytophthora spp., outbreeding was reported as a possible mechanism generating new pathotypes able to overcome host resistance [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preferences of particular isolates to produce either antheridia or oogonia in heterothallic species have been recorded; however, bisexuality is hypothesised in homothallic species [ 29 ], therefore, the possibility of the mating of two isolates of homothallic species cannot be excluded. Outbreeding was documented in either heterothalic P. infestans [ 30 , 31 , 32 ] or P. ramorum [ 33 ], or in homothallic species such as P. sojae and P. porri . In homothallic Phytophthora spp., outbreeding was reported as a possible mechanism generating new pathotypes able to overcome host resistance [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional agriculture, late blight is primarily controlled using protective agents or systemic fungicides. However, pesticides pollute the environment and accelerate the development of tolerance and the mutation of Phytophthora infestans (Maurice et al, 2009). Risch and Merikangas (1996) and Hansen et al (2001) first reported genome-wide association analysis (GWAS).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic reprogramming in plants also can be triggered by abiotic constrains (Wibowo et al, 2016;Lämke and Bäurle, 2017) and if applicable to P. infestans, such a function could generate increased opportunities to adapt to various changes in climate conditions. The extent of genetic variation in Scandinavian P. infestans populations has been debated (Maurice et al, 2019). Beside different marker systems employed for the analysis by different research groups, variation in the observations may as well reflect epigenetic influences driven by annual climate fluctuations.…”
Section: Discussionmentioning
confidence: 99%